Analyse de réminiscences à l’occasion d’émotions et subjectivation du travail - Long Pham Quang (Éducation et Socialisation)
The article makes restitution of some results obtained during a research concerning the study of the learning of the future mortuary staff in working place. It is aimed more specifically to understand the role that the phenomena of reminiscences could play in the process of learning of mortuary care on the occasion of emotions arising from the trainee. This study uses data of observations and interviews of autoconfrontation. The purpose is to identify reminiscences put in words by the trainee, to explore their contents and to analyze how they can be connected with learning which the subjective dimension is particularly pointed. In this context, the contribution reflects a dual challenge, first to try a conceptual clarification on the notion of reminiscence in the fact that it happens and then a methodological approach aiming to report traces of these reminiscences in the words of the trainee.